COMPETITIVE ABILITY OF BEAN CULTIVARS WITH HAIRY BEGGARTICKS - Galon, Leandro (2017)
Weed interference is a factor that limits the productivity of beans and, among these, hairy beggarticks is one of the main species competing with the crop for environmental resources. Thus, the aim of this study is to evaluate the competitive ability of black bean cultivars (BRS Campeiro, IPR Uirapuru, SCS204 Predileto and BRS Supremo) in the presence of a biotype of hairy beggarticks. The experimental design is a completely randomized block with four replications. Treatments were arranged in a replacement series, consisting of a proportion of the crop and the hairy beggarticks: 100:0; 75:25; 50:50: 24:75, and 0:100, which corresponds to 40:0, 30:10, 20:20, 10:30, and 0:40 plant pots1. We accomplished competitive analysis through diagrams applied to the replacement series, as well as using relative competitive indices. The leaf area and shoot dry mass were evaluated at 40 days after emergence of the species. There was competition between bean cultivars and hairy beggarticks for the same environmental resources, causing negative interference in the growth of the species, independent of the proportion of plants. Bean cultivars had a lower relative loss by reducing the morphological variables of the hairy beggarticks, thereby demonstrating superiority in its competitive ability in relation to the weed. Interspecific competition is less damaging than intraspecific competition for both species.